Superheater Tube Flat Wall Stationary Temperature Field; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Parpiev A. T. (2016, 2016)
Title screen